Evaluasi Kegiatan Sub Bagian Data dan Informasi Pada Gugus Tugas COVID 19 di Kabupaten Tulungagung - Ratih Cahyaning Tyas (Media Gizi Kesmas, 2022)
Background: Coronavirus Disease 19, commonly dubbed as COVID-19, has been widely spread across the globe since March 2020, and WHO has declared it a Pandemic. In Indonesia, the disease began to spread in June 2020. The spreading rate was so fast that it reached every part of the country, including the Tulungagung district in East Java. The Government of Tulungaggung has tried to curb the rapid spread of COVID-19 cases by establishing the "COVID-19 Handling Task Force Team”. The author was assigned in Data and Information in the task force, and of course, the performance is far from perfect. Therefore, an evaluation to measure the success rate of the programs conducted by the Sub Department of Data and Information of the COVID-19 Handling Task Force Team in Tulungagung District was made.Objectives: The purpose of this study was to evaluate the activities of the data and information sub-section on the Covid-19 task force in Tulungagung Regency.Methods: The works performed by volunteers in the COVID-19 Handling Task Force Team of Tulungagung District were observational participative, where the students are actively involved in controlling the cases. The students were given the task of the data and information. The primary responsibility of the data and information department is the evaluation of monitoring, information systems, and press release activities.Results: This final assignment/mini-thesis covers the implementation of activities at the Sub Department of Data and Information contains ten measured activities. The measurement was made by comparing the actual performance with the guideline in place.Conclusions: In conclusion, the analysis of activities at the Sub Department of Data and Information was made to 10 activity indicators. The result is that each indicator are consistent and aligned with the prevailing guidelines such as Ministry of Health Regulation number 45 of 2014 concerning Health Surveillance Implementation, COVID-19 Prevention and Control Guideline of 2020, and Behavior Change Communication (KPP) strategy in COVID-19 preventions.